PENERAPAN PASAL 281 KUHP TENTANG TINDAK PIDANA ASUSILA YANG DILAKUKAN OLEH MILITER. (STUDI KASUS PUTUSAN PENGADILAN MILITER NOMOR 127-K/PM.II-09/AD/VIII/2017) - Rifki Yuditya Saputra; Sugandi Ishak (Jurnal Hukum Adigama, 2019)
Decency crimes are interpreted as an act that violates courtesy, politeness, order, customs which can result in the creator being convicted. A Military who commits a crime other than being enforced by the Criminal Procedure Code also applies the KUHP because the KUHPM is a specialist lex from the KUHP. The moin prblem in this research is How is the application of Article 281 of the KUHP with the principle of Lex Specialis Generali Deregate about decency crimes committed by the Military ?, Can criminal penalties be applied to members of the military who commit decency crimes ?. Type of normative juridical law research. Basically the Criminal Procedure Code is a legal provision that regulates a military about which actions constitute a violation or crime or is a prohibition or necessity and is given a threat in the form of criminal sanctions against violators. The imposition of punishment for the military that commits a crime is the existence of an additional criminal which is military in nature. And in that case whether criminal offenses can be applied to members of the military who commit decency acts. The reasons for the existence of the KUHPM are lex specialis of the KUHP even though in the KUHP as stipulated in Article 52 concerning the weighting of criminal threats, the criminal threat stipulated in the KUHP is still felt to not fulfill a sense of justice for TNI members. Therefore, it needs to be regulated in the KUHPM specifically to regulate specific matters.